2014
DOI: 10.1080/08927022.2014.895001
|View full text |Cite
|
Sign up to set email alerts
|

Establishing trends in ion adsorption on the aqueous aluminium hydroxide nanoparticle Al30

Abstract: The fact that chemical reactions at environmental interfaces are becoming accessible to quantum mechanical computational studies provides geochemical researchers with a new means to predict properties that cannot readily be measured and to develop molecular-level understanding of geochemical model systems. Recent computational studies of Cu 2þ and SO 22 4 adsorption onto the Keggin-based aqueous aluminium nanoparticle (Al 30 O 8 ðOHÞ 56 ðH 2 OÞ 18þ 26 ), or Al 30 , revealed opposing trends in adsorption site p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Modelling ionic sorption mechanisms on surfaces is key to understanding a wide range of physical phenomena in catalytic chemistry [1][2][3][4][5] , biochemistry 6,7 , energy storage 8,9 and environmental chemistry, where modelling has been used to study the migration of ion contaminants in soils and sediments, [10][11][12][13][14][15][16] and the treatment of polluted water with adsorbent materials [17][18][19] . Computational studies can provide insight into ion/surface interactions at the molecular level by predicting preferred reaction sites, 2,4,5,14,17 calculating the most stable structures during the interactions 1,9,14,19 and allowing comparison of the interaction energies of competing species 15,18,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Modelling ionic sorption mechanisms on surfaces is key to understanding a wide range of physical phenomena in catalytic chemistry [1][2][3][4][5] , biochemistry 6,7 , energy storage 8,9 and environmental chemistry, where modelling has been used to study the migration of ion contaminants in soils and sediments, [10][11][12][13][14][15][16] and the treatment of polluted water with adsorbent materials [17][18][19] . Computational studies can provide insight into ion/surface interactions at the molecular level by predicting preferred reaction sites, 2,4,5,14,17 calculating the most stable structures during the interactions 1,9,14,19 and allowing comparison of the interaction energies of competing species 15,18,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have revealed strong outer-sphere ion pair formation for ions in the beltway. 28 Extending this knowledge to the (TBP)2Al30-S structure, we intuit that Step 1 of the EW mechanism (Scheme 7.1) drives the beltway site preference, and subsequent ligand exchange then results in the final inner-sphere ion pair. It is noteworthy that oxygen functional group type and coordination alone cannot explain the greater reactivity of adsorption sites in the Al30 beltway region, even though such arguments have been successfully applied to a variety of mineral surface reactivities.…”
Section: Discussionmentioning
confidence: 96%
“…25,26 Further details of the computational methods (including benchmarking and convergence studies for Al30) are reported in our previous work. 28,29 The initial isolated molecular structure for Al30 was based on the experimental crystal structure, which has been reported previously. 20,53,66 Based on bond valence analysis, 95 the molecular formula of Al30 is expected to be (Al30O8(OH)56(H2O)26) 18+ , and the molecule has inversion symmetry.…”
Section: Computational Methodologymentioning
confidence: 99%
See 2 more Smart Citations